BAB130: Arabic Language for Tourism I / Academy of Language Studies - UiTM, Academy of Language Studies (2018)
This course is an extension from the Elementary ArabicTAC151 and it is offered only to students of the Diploma in Tourism Management. It focuses on the learning of the Elementary Arabic for a specific purpose that is tourism. In this course, students are exposed to terminologies, phrases, sentences, dialogues and clippings as well as cultural elements that are directed to dealings / transactions / communication and activities in tourism.